Analisis Perbedaan Lama Persalinan Kala II pada Ibu Primipara Usia Dini dengan Usia Ideal di TPMB Bd. Delima, S.Keb Kota Cimahi Tahun 2023 - wisdyana, Wisdyana Saridewi; Mallino Azzahra , Larasati; Rosyeni , Yeni (JURNAL KESEHATAN KARTIKA, 2024)
Background: Childbirth is the process of expelling a baby from the mother's womb which involves a series of stages, including uterine contractions that develop gradually, opening the cervix, and pressing the baby through the mother's birth canal. The stages of labor consist of stage I, stage II, stage III and stage IV. Based on case data recorded at the Cimahi City Health Service, in Padasuka Village, cases involving pregnant women and women giving birth too young in 2020-2022 have increased by 10.42%. Objective: The aim of this study was to determine the difference in length of second stage of labor between early age primiparous mothers and those at ideal age at TPMB Bdn. Delima, S.Keb in 2023 in Cimahi City. Method: The design of this research is comparative analytical and uses retrospective data. This study used a sample of 44 mothers giving birth who were recorded in the birth register book at TPMB Bd. Delima, S. Keb Cimahi City. The data used in this research is secondary data in 2023 which was obtained using an observation sheet which includes the mother's initials, age and also the length of the second stage of labor. Univariate data analysis using the mean formula and bivariate analysis using the independent t test. Results: The average length of second stage of labor in early age primiparous mothers was 66.05 minutes, the average length of second stage of labor in ideal age primiparous mothers was 41.50. The results of parametric statistical tests using the independent t test obtained a p value of 0.000. Conclusion: There is a difference in the length of the second stage of labor between primiparous mothers of early age and ideal age.